Paleogeography of the lower Taravu Valley during Late Holocene (SW Corsica). (10th March 2023) - Vella, Marc-Antoine
Abstract: The Taravu valley, located in the south-west of Corsica, is one of the most extensive watersheds on the island. Recent paleoenvironmental studies allowed to restitute the chronostratigraphy of the two ponds in the lower valley. However, the paleogeographic evolution of this sector still remains largely to be specified. In order to reconstruct the transformations of the landscape of the lower Taravu valley during the Late Holocene (2250 BCE), we have developed an innovative interdisciplinary approach combining the methods of historical geography (ancient maps and aerial photographs), geoprocessing of topographic data (slope map and drainage map) that we associated with the results of an electromagnetic survey (EMI) and previous stratigraphic data. This synthesis enables the creation of a geomorphological map of the lower Taravu valley, to identify several major landscape changes since the Neolithic period (5800-3000 BCE), and to follow the evolution of the alluvial forms of the Taravu and the shore line since the end of the 18th c. CE.